If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1y + -15y + -4y + 13y + 2y = 20 Combine like terms: -1y + -15y = -16y -16y + -4y + 13y + 2y = 20 Combine like terms: -16y + -4y = -20y -20y + 13y + 2y = 20 Combine like terms: -20y + 13y = -7y -7y + 2y = 20 Combine like terms: -7y + 2y = -5y -5y = 20 Solving -5y = 20 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-5'. y = -4 Simplifying y = -4
| -1(1-4x)=-22+x | | k^2+6+5k=0 | | 96-n=-23 | | 7q=9(q+4) | | 6-4x=-9x+8 | | 12+(-3)+(-1)= | | H=120t-16t^2 | | 1/4x-37.25=52.50 | | 8(-27)-11= | | y-8x=12 | | 2m-7=8+2m | | 2800=460+65m | | 2^20/2^3 | | 4=k/6 | | 4g-2g-g=10 | | -(1-4x)=22+x | | 2y-6x-12=0 | | 5/7x=40.5 | | 3m+-19=14 | | (y^2/3)^-9 | | 3m-19=24 | | 8*n=80 | | 6y+2x-y-x= | | .2/10 | | 3x-4x+2x+1-3= | | 9x^2+30x+1=0 | | 2x^2+10=98 | | 3/6x=35 | | -y=6x+4 | | (20x^2y^9z^-6/12x^-5y^-9z^-3)^-1 | | 3(3x+9)+3(3x+15)=9 | | 2(2x+8)+4=5x+4 |